An adjustable closed-loop liquid-based thermoelectric electronic cooling system for variable load thermal management. (May 2019) - Siddique, Abu Raihan Mohammad; Muresan, Heman; Majid, Shaikh Hasibul; Mahmud, Shohel
Highlights: An alternative way to increase liquid cooling performance for electronic components. A liquid-based thermoelectric cooling system was designed and developed. The proposed and the commercial system were compared experimentally. Different liquids were used for cooling system to enhance the thermal performance of the system. COPs were 2.8 and 3.21 for commercial and TE systems respectively. Abstract: Electronic components have been experiencing a rapid rise in power densities in a constrained size which can cause relatively high amounts of heat generation inside it. Such internal heat generation is the primary reason for component failure. Therefore, it is very important to develop a high-performance yet the economical cooling system for electronics which can be a suitable thermal solution to remove the generated heat from a tested electronic component and elongate their operational lives. In this work, a closed loop liquid-based thermoelectric electronic cooling (LTEEC) system is developed which is adjustable to variable thermal load. Although cooling is the primary function of the designed system, it can be reversed to a heat pump mode if required. The performance of the developed system was investigated experimentally and compared to a commercial system. The comparisons were accomplished by observing the temperature rise as a function of time and the calculated coefficient of performances (COPs) for each system. For example, for a 16.7 W generated heat in a test component, the developed LTEEC system can reduce the hot side temperature 4 °C more than the commercial system. The COP of the LTEEC system (e.g., 3.21) is found to be better than the commercial system (e.g., 2.81). Furthermore, different liquids with different weight ratios were tested with the proposed LTEEC system to determine economical alternatives to water in order to improve its performance. The proposed system is comparatively easy to construct and costs ($30) less than the commercial system.